Pengaruh Pemberian Mulsa Organik Alang-Alang Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Kedelai (Glycine Max L) - Faisal Rizki; Khusnu Abdillah Siregar; Muhammad Alfatih (Fakultas Pertanian Universitas Ratu Samban, 2025)
Soybean yields in Rokan Hulu continue to increase along with the increasing population and the increasing diversity of basic soybean growth, the increasing demand for soybeans is not accompanied by growth by Rokan Hulu farmers, this is due to the decreasing area of ​​land that can be planted with soybeans and low soil fertility, so efforts need to be made towards the growth and yield of soybeans, it is hoped that the use of organic mulch of alang-alang can increase soybean yields. This study was conducted to determine the effect of giving several doses of organic mulch of alang-alang on the growth and yield of soybeans. This study used a Randomized Block Design (RAK) with 5 treatments, each treatment had 4 groups of plants, where each plot consisted of 10 plants. The treatments are P0 = without organic mulch of cogongrass, P1 = organic mulch of cogongrass 5.6 kg, P2 = organic mulch of cogongrass 7.2 kg, P3 = organic mulch of cogongrass 8.8 kg, P4 = organic mulch of cogongrass 10.4 kg. The variables observed were plant height, leaf width, number of plants, flowering age, harvest age, number of filled pods, wet seed weight, dry seed weight, weight of 100 seeds. The results of this study were seen from the results of the Duncan multiple distance test (DMRT a 5%). The provision of organic mulch of cogongrass on soybean plants had a significant effect on harvest age, flowering age, number of filled pods, wet seed weight, dry seed weight, weight of 100 seeds and had no significant effect on plant height, leaf width, number of leaves. This is due to the suboptimal nutrients given to the soil. The provision of organic mulch of alang-alang grass with a dose of 8.8 kg tends to affect the growth and yield of soybean plants.